Squamous odontogenic tumor in a cat – case report - Malegoni, Ana Clara Santana; Lemos, Virgilio Zoppi; Cota, Jessica Miranda; Gava, Maylla Garschagen; de Souza, Mayara Coutinho Carlos [UNESP]; Merísio, Alice Corrêa Rassele [UNESP]; de Barros, Séfora Vieira da Silva Gouvêa; Moscon, Luiz Alexandre; Pereira, Clairton Marcolongo (My University, 2021)
The present work reports a case of a squamous odontogenic tumor (SOT) in a mixed breed feline. The animal had hyporexia, sialorrhea and increased volume in the right mandibular branch. The parameters evaluated during the clinical examination were in accordance with the normal values for the species. In the full blood count (FBC) and serum biochemistry, no changes were observed. An X-ray of the skull showed a marked bone lytic reaction and a proliferative aspect in the right mandible. Hemimandibulectomy was performed and the removed material was sent for histopathological examination, in which a squamous odontogenic tumor was diagnosed. All tumors originating from odontogenic tissues are considered benign. SOT arises from remnants of the dental lamina and occurs equally in the mandible and maxilla. It is located predominantly in the posterior region of the mandible, and more rarely in the anterior region of this tissue. This neoplasm is taken as quite rare in the human medical literature and citations of this tumor is lacking in the veterinary medicine.
Keywords: Feline; Histopathology; Odontogenic Tumor